Interactions between the Transmembrane Segments of the Alphavirus E1 and E2 Proteins Play a Role in Virus Budding and Fusion - Sjöberg, Mathilda (American Society for Microbiology, 2003)
The alphavirus envelope is built by heterodimers of the membrane proteins E1 and E2. The complex is formed as a p62E1 precursor in the endoplasmic reticulum. During transit to the plasma membrane (PM), it is cleaved into mature E1-E2 heterodimers, which are oligomerized into trimeric complexes, so-called spikes that bind both to each other and, at the PM, also to nucleocapsid (NC) structures under the membrane. These interactions drive the budding of new virus particles from the cell surface. The virus enters new cells by a low-pH-induced membrane fusion event where both inter- and intraheterodimer interactions are reorganized to establish a fusion-active membrane protein complex. There are no intact heterodimers left after fusion activation; instead, an E1 homotrimer remains in the cellular (or viral) membrane. We analyzed whether these transitions depend on interactions in the transmembrane (TM) region of the heterodimer. We observed a pattern of conserved glycines in the TM region of E1 and made two mutants where either the glycines only (SFV/E1(4L)) or the whole segment around the glycines (SFV/E1(11L)) was replaced by leucines. We found that both mutations decreased the stability of the heterodimer and increased the formation of the E1 homotrimer at a suboptimal fusion pH, while the fusion activity was decreased. This suggested that TM interactions play a role in virus assembly and entry and that anomalous or uncoordinated protein reorganizations take place in the mutants. In addition, the SFV/E1(11L) mutant was completely deficient in budding, which may reflect an inability to form multivalent NC interactions at the PM.